Relationships Between Positive Leadership Styles, Psychological Resilience, and Burnout: An Empirical Study Among Turkish Teachers - Gaye Onan; Lütfi Sürücü; Mustafa Bekmezci; Alper Bahadır Dalmış; Gözde Sunman (Behavioral Sciences, 2025)
Given the rising workloads and increased risks of burnout across various industries, enhancing employee resilience and well-being has become increasingly important. This study investigates the impact of positive leadership styles—servant, authentic, and transformational leadership—on psychological resilience and burnout levels. While prior research has examined the isolated relationships between leadership, resilience, and burnout, few studies have analyzed these variables collectively within an integrated theoretical framework. To address this gap, the present study integrates insights from the Leader–Member Exchange (LMX) theory, the Conservation of Resources (COR) theory, and the Job Demands–Resources (JD-R) model to provide a comprehensive perspective. Data were collected from 387 private school teachers in Turkiye. Statistical analyses were conducted using PROCESS Macro (Model 4), assessing both direct and mediating effects. The findings reveal that all three leadership styles enhance psychological resilience and mitigate burnout. Furthermore, psychological resilience partially mediates the relationship between positive leadership styles and burnout. These results contribute to the literature by demonstrating how positive leadership can buffer against burnout through resilience, emphasizing the need for context-specific research in the field. This study also offers practical implications for managers seeking to foster supportive work environments.